Spatiotemporal variability of atmospheric blocking within Northern hemisphere of Euro-Atlantic sector during 1976-2015 - Самчук, Є. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2018)
Formulation of the problem. The westerly jet and the eastward progression of baric systems are common states of atmosphere in Northern hemisphere’s midlatitudes. But this persistence balance is frequently interrupted by long periods of atmospheric blocking, which is a large-scale quasi-stationary extratropical flow regime. As a specific state of circulation it causes major transformation of baric, thermal and wind in the low and middle troposphere and also affects cyclonic activity in nearby regions. On the local scale blocking can be associated with extreme weather such as droughts in summer and severe cold spells in winter. Also, redistribution of heat and precipitation, caused by blocking events, allows us to consider blocking as a climate factor. However, even now, after decades of study, blocking onset and decay are not well understood, as well as basic blocking theory wasn’t formulated either.The purpose of the article. Complete study of the atmospheric blocking phenomena requires an objective criterion for blocking anticyclones identification. Such criterion is based on preceding identification and tracking of baric systems throughout low and middle troposphere, which allows us to take into account its vertical structure. This approach is far more direct than existing blocking indices which use indirect evidences of atmospheric blocking existence. Defined criterion takes into account anticyclone’s lifetime duration, mean latitude and longitudinal displacement.Methods. The author’s own achievements made the methodical basis for the article.Results. Using a defined criterion, a dataset of atmospheric blocking episodes, occurred during 1976-2015, was created. It contains both detailed and generic characteristics of 210 blocking anticyclones. For case study methods of baric system’s parameters evaluating were developed. These parameters include such characteristics as blocking intensity, affected area and accumulated geopotential anomaly. Analysis of these characteristics shows stable regularity of blocking episode’s spatiotemporal variability. Spatial analysis shows presence of three major cells of atmospheric blocking in Euro-Atlantic sector: Atlantic, Scandinavian and Caspian. Parameters of blocking anticyclones in each cell show different behavior, but common trend is decrease in blocking activity in the last ten years comparing to the rest of research period.Scientific novelty and practical significance. New approach to the atmospheric blocking study was realized and regional features of spatial distribution of blocking episodes in Europe were discovered for the first time. These features will be used in detailed study of the atmospheric blocking’s effect on regional weather regime and climate.